Management of Soft Tissue Injuries of the Face* - Gautam Biswas (Indian Journal of Plastic Surgery)
Maxillofacial injuries now account for a large segment of patients in the casualty. This being, because of the increase in high speed vehicular traffic. A study conducted for one year, in 1983, showed that out of a total of 411 patients treated, 40% were those of soft tissue injuries of the face. Management of these wounds, after noting their site, character and time following injuries, to obtain optimum results, were carefully assessed. Gentle handling of tissues, using non reactive suture materials with accurate reorientation, gave the best results.